Smoking and COVID-19 infection and related mortality: a prospective cohort analysis of UK Biobank data - Prats Uribe, A; Xie, J; Prieto Alhambra, D; Petersen, I (Dove Medical Press, 2021)
Background Several papers have shown contradictory evidence about the relationship between smoking and COVID-19 related deaths. There is little evidence about smoking and risk of infection. We aim to examine association between smoking and COVID-19 infection and subsequent mortality. Methods Prospective study with participants from the UK Biobank cohort. Participants who lived in England were followed up from 01/02/2020 to 28/06/2020 with data linked to hospital episode statistics, office for national statistics and Public Health England PCR tests. We compared current-smokers, previous-smokers with never-smokers and estimated risk ratio (RR) of COVID-19 infection and subsequent mortality using Poisson regression adjusting for age, sex, ethnicity, body mass index and socio-economic status. Interactions between smoking status and age and sex were tested for using multiplicative interactions, and analyses were stratified by median age (49-68 years, 69-86 years) and sex. Results In total, 402,978 participants were included in the analyses. The majority were never smokers, 226,294 (56.2%), 140,090 (34.8%) were previous smokers, and 39,974 (9.9%) current smokers. COVID-19 infection was identified in 1,591 (0.39%) people, and 372/1,591 (23.4%) died. Amongst the younger participants, smokers were nearly twice as likely to become infected with COVID-19 than never smokers (RR 1.88 [1.49 – 2.38]) whereas there was no difference for those aged 69+ (RR 1.05 [0.82 – 1.34]). In contrast, amongst the older participants smokers were twice as likely to die from COVID-19 compared to non-smokers (RR 2.15 [1.11 – 4.16]) whereas there was no difference for those under the age of 69 (RR 1.22[0.83 – 1.79]). Similar patterns were observed for previous smokers. The impact of smoking was similar in men and women. Conclusion The association between smoking and COVID-19 infection and subsequent death is modified by age. Smokers and previous smokers aged under 69 were at higher risk of COVID-19 infection, suggesting the risk is associated with increased exposure to SARS-COV-2 virus. Once infected, older smokers were twice as likely to die from COVID-19 than never smokers, possibly mediated by increased risk of chronic conditions/illnesses.